(untitled) (KASBIT Business Journal, 2022)
Islamic Banking in Pakistan has been continuously growing since 2001 and currently, five full fledge Islamic Banks are working. This study has investigated the inside factors which effect Islamic Banks’ profitability. These internal factors include Capital Adequacy Ratio, Deposit ratio, operating expense with total assets ratio, Size, and Debt to Equity Ratio, and were taken as Independent variables in this study, whereas profitability return on asset was taken as a dependent variable. This study has covered the period of 2015-2020 and data was gathered from financial reports of Islamic Banks, previous studies which were conducted in Pakistan did not cover up to 2020 and mostly covered both internal and external factors but in this research, we have emphasized on internal factors exclusively. Panel Data was analyzed with step-by-step statistical techniques like POLS, BRUESCH-PAGAN TEST, RANDOM EFFECT, and HAUSMAN TEST and finally, Fixed Effect Model was applied through EViews version-11. According to the investigated results of this study, two independent variables capital adequacy and operating expense ratio had a positive and major influence on return on assets (Dependent Variable). Hence null hypothesis of these variables was rejected and concluded that only the capital adequacy ratio and operating expenses with total assets ratio positively affected Islamic banking profitability.